Correlation between Empowering Leadership and Generation Z Decision Making in Politics during the COVID-19 Pandemic - Herlina Harsono Njoto; Suryanto Suryanto (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
This research is aim to see the correlation between leadership and Generation Z decision making in politics during the COVID-19 pandemic. The criteria for the subjects in this study is Generation Z from 17 to 26 years old. This study is using non probability observation with the purposive sampling techniques. Respondent have a total 119 Generation Z. The scale to measure the correlation of leadership is used the Empowering Leadership Questionnaire scale from Arnold, et al (2000) was transadaptation into Indonesia and have a realibility value of 0.959. Decision making will be measured by Decision Making Scale from Scott and Bruce (1995) that have a reliability value of 0.866. Analyzed of the data performed by simple- linear regression techniques. The result of the data concluded that there were was a positive correlation between empowering leadership and decision making in Generation Z during the COVID-19 pandemic because the results of simultaneous hypothesis showed the coefficient r is 0.288.